Hyophila flavolimbata, a new species of Pottiaceae from northwestern Yunnan, China - He, Si; Yi, Yan-Jun; Ma, Wen-Zhang (Phytotaxa, 2015)
A new species of Pottiaceae, Hyophila flavolimbata S. He & Y.-J. Yi, is described and illustrated from northwestern Yunnan Province, China. The new species is most similar to H. involuta in having spathulate leaves with non-papillose leaf cells and two stereid bands in costa. Its distinguishing characteristics include a differentiated leaf margin bordered by 3–4 rows of lightly yellowish thick-walled cells, leaf cells completely plane on both abaxial and adaxial leaf surfaces, papillose stem epidermal cells, a layer of pseudoleptoids developed next to hydroids in central strand, and the presence of subguide cells in costa.